العرف عند الأصوليين ونماذج من تطبيقاته الفقهية - الرفاعي، أنس محمود توفيق العواطلي (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنين بالقاهرة, 2019)
لقد عد علماء الأصول العرف مصدراً من مصادر التشريع الإسلامي عند عدم وجود النص، أو في تخصيصه للنص العام. وقد تتغير الأحكام التي بنيت على العرف بتغير الزمان والمكان، بحسب أحوال الناس. فجاءت هذه الدراسة لتلقي الضوء على أن العرف دليل من الأدلة على الأحكام الشرعية، وذلك من خلال توضيح بعض النماذج، كالحرز، وقطع النباش ومقدار كسوة الكفارة في اليمين وغيرها.. والتي فيها مصالح للعباد لا تتضارب مع النصوص الشرعية. وقد انبني البحث على مقدمة وثلاثة مباحث وخاتمة؛ كان الأول منها في بيان حقيقة العرف؛ وذلك بمعرفة معناه في اللغة، ثم تعريفه اصطلاحاً وكيفية اعتباره دليلاً من أدلة الأحكام، والمبحث الثاني في أقسام العرف، وأن الأحكام تتغير باختلاف العوائد والأحوال، وأما المبحث الثالث فكان في بعض النماذج والتطبيقات الفقهية التي بنيت على العرف، ثم جاءت الخاتمة فيها أهم نتائج البحث.
Scholars of fundamentals have considered the concept of custom a source of Islamic legislation when there is no text, or in case of specifying the general text. Provisions of law based upon customs may be altered in terms of time, space, and people's circumstances. Accordingly, this research sheds light upon the fact that a custom is an evidence of the jurisprudential provisions. Such notion can be achieved through clarifying certain models as the sanctuary, cutting the hands of grave robbers and the prescribed expiation of an oath …etc., for the best of people and at the same time it is in no conflict with the provisions of Islamic law. The research consists of an introduction, three chapters and a conclusion. The first chapter is dedicated to display the truth of custom as a concept tracing its meaning in Arabic, then defining it as a term and how it is considered an evidence of the jurisprudential rulings. The second chapter handles the changes that come over provisions of law in terms of circumstances and conditions. The third chapter examines some models and jurisprudential applications that have been based upon the customs. Finally, the conclusion includes the most important results.
Keywords: الشريعة الإسلامية -- أصول الفقه -- مقاصد الشريعة -- العرف -- الأحكام الشرعية